Transforming mass production contact centres using approaches from manufacturing - Smith, Marisa K.; Ball, Peter D.; Bititci, Umit S.; van der Meer, Robert (MCB University Press, 2010)
PurposeThe purpose of this paper is to identify theories from manufacturing which can be applied to alleviate current issues within contact centre organisations. As contact centres currently adopt a mass production approach to customer service, this paper aims to examine the key issues currently facing contact centres and investigate how manufacturing has overcome some of its issues with the mass production approach. Design/methodology/approach The research employs a qualitative case study approach using a cross section of different types of contact centre to identify the current issues with contact centres. Interview and direct observation are the chosen methods for data collection and the data is analysed using a series of deductive and emergent codes. FindingsFrom empirically investigating the issues that contact centres are currently facing it would imply that they have the same issues as manufacturing historically faced. Therefore, we can conclude that if manufacturing can develop from an industry founded on scientific management principles then so can the contact centre industry. Research limitations/implicationsThe findings of this research provide a useful starting point to discuss the ability of theories developed in manufacturing to be adapted into the contact centre context. This research is a starting point for further work into the applicability of manufacturing theories into the contact centre environment and as such it is deliberately discussed at a high level of abstraction. Practical implicationsMany of the techniques employed in contact centres originate from manufacturing's past but little of the research focuses on how contact centres can learn from manufacturing's future therefore this paper has practical implications in identifying which concepts can be transferred from manufacturing to contact centres. Originality/valueThe value of this paper is that it looks to the future of contact centre operations and discusses which techniques can be transferred from manufacturing to alleviate some of the current issues with contact centres.
Keywords: Call centres, Operations management, Case studies, Customer service management